(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Management of disk scheduling is a very important aspect of operating system. Disk scheduling involves a careful examination of pending requests to determine the most efficient way to serve these requests. A disk scheduler examines the positional relationship among waiting requests, then reorders the queue so that the requests will be serviced with minimum seek. Performance of the disk scheduling completely depends on how efficient is the scheduling algorithm to allocate services to the request in a better manner. After the arrival of the multi-core processor, the speed of the processors became much faster with the Hyper-Threading technology, and with this the speed of the processors increased dramatically with a record speed. All processers need CPU time and read/write time together to complete their execution. Read/write operations require the operating system to access the disk to store and retrieve data. In the recent years many algorithms (FIFO, SSTF, SCAN, C-SCAN, LOOK, etc.) are developed in order to optimize the system disk I/O performance. The purpose of this study is to obtain a new scheduling algorithm that reduces seek time, sum of head movement, spin time, and transfer time, so as to improve disk performance efficiency in a better way to try to synchronize with CPU performance.